Patient state index and cerebral blood flow changes during shoulder arthroscopy in beach chair position - Buget,Mehmet Ilke (2016)
Abstract Background and objectives: The aim of the study were to demonstrate the possible hemodynamic changes and cerebral blood flow alterations in patients who were positioned from supine to beach chair position; and to detect if the position change causes any cortical activity alteration as measured by the 4-channeled electroencephalography monitor. Methods: 35 patients were included. Before the induction, mean arterial pressure and patient state index values were recorded (T0). After the intubation, doppler-ultrasonography of the patients’ internal carotid and vertebral arteries were evaluated to acquire cerebral blood flow values from the formula. In supine position, mean arterial pressure, patient state index and cerebral blood flow values were recorded (T1) and the patient was positioned to beach chair position. After 5 min all measurements were repeated (T2). Measurements of patient state index and mean arterial pressure were repeated after 20 (T3), and 40 (T4) min. Results: There was a significant decrease between T0 and T1 in heart rate (80.5 ± 11.6 vs. 75.9 ± 14.4 beats/min), MAP (105.8 ± 21.9 vs. 78.9 ± 18.4 mmHg) and PSI (88.5 ± 8.3 vs. 30.3 ± 9.7) (all p < 0.05). Mean arterial pressure decreased significantly after position change, and remained decreased, compared to T1. The overall analysis of patient state index values (T1-T4) showed no significant change; however, comparing only T1 and T2 resulted in a statically significant decrease in patient state index. There was a significant decrease in cerebral blood flow after beach chair position. Conclusion: Beach chair position was associated with a decrease in cerebral blood flow and patient state index values. Patient state index was affected by the gravitational change of the cerebral blood flow; however, both factors were not directly correlated to each other. Moreover, the decrease in patient state index value was transient and returned to normal values within 20 min.